Pengaruh Pemberian Antioksidan terhadap Kadar Interleukin 1 Beta pada Osteoartritis: Sebuah Tinjauan Sistematis - Panji Sananta; Respati Suryanto Dradjat; Galuh Ayu Ratna Savitri; Lasa Dhakka Siahaan (Jurnal Biomedika dan Kesehatan, 2026)
Osteoarthritis (OA) is a degenerative joint disease characterized by pain, inflammation, and impaired physical function. Interleukin-1 beta (IL-1β) plays an important role in OA pathogenesis by promoting inflammatory and catabolic processes within the joint. Antioxidants have shown potential in modulating oxidative stress and inflammatory responses associated with OA. This systematic review evaluated the effects of antioxidant administration on IL-1β levels in knee osteoarthritis. A systematic literature search was conducted in five databases (PubMed, Cochrane Library, Epistemonikos, Scopus, and ProQuest) until January 2025, following PRISMA guidelines. Eligible studies included intervention studies involving human or animal models of knee OA, antioxidant administration, and assessment of IL-1β outcomes. Because of substantial heterogeneity among studies, a qualitative synthesis was performed. Risk of bias was assessed using the RoB 2.0 tool for randomized controlled trials and the SYRCLE tool for animal studies. A total of 13 studies were included, consisting of six randomized controlled trials and seven animal studies. Most studies demonstrated reductions in IL-1β levels or expression following antioxidant administration, including curcumin, vitamin E, resveratrol, cucumber extract, and L-carnitine. Several studies also reported improvements in inflammatory markers, pain, and cartilage-related outcomes. Overall, the included studies showed a low risk of bias. Current evidence suggests that antioxidants may reduce IL-1β levels and exert anti-inflammatory effects in knee OA. However, further well-designed clinical studies are needed to confirm their efficacy and safety.